Análisis de la maternidad forzada y derechos fundamentales de niñas, adolescentes y mujeres víctimas de violación en el Ecuador - Doménica Cecilia, Chávez Sánchez (2020)
This research aims to respond to a current legal and social problem, the decriminalization of abortion in cases of rape is a recurring theme and has different conceptions, taking into account the different legal ideological currents and in the same way raises solutions through the Criminal doctrine based on guaranteeism, it is for this reason that the main objective of this study is to analyze how forced motherhood or forced pregnancy violates fundamental rights of those who have been victims of sexual violence. It is an investigation that has a novel methodology, which is applied from the perspective of the victim of sexual violence and that is also useful, since it intends that future investigations be carried out within the same feminist methodological line, it intends that it be taken into It counts as being victims of a crime committed against them, they can also be criminalized for deciding not to continue with a pregnancy as a result of the violence they have suffered, without there being real and effective alternatives that guarantee their fundamental rights by the State and also by justice operators.